The length of the development phases and the growing season of Nigella sativa L. along altitude gradients (the example of Dagestan) - L. A. Gabibullaeva (Юг России: экология, развитие)
Aim. To study of the duration life cycle and phenological phases of plants  of Nigella sativa L. (variability depending on height above sea level, seed  quality and climatic conditions of the year). Material  and Methods.  Generally  accepted  methods described  in  the  relevant guidelines were used in conducting the research. Samples of  Nigella sativa (black cumin) were sourced from various eco‐geographical  origins: Saudi Arabia, Ethiopia, Syria, Egypt and Azerbaijan.  Results. It was determined that with an increase in height above sea level  of the place of growth, the life cycle of plants of N. sativa samples is  prolonged and their content of palmitic acid decreases.  Conclusion. The main reason for the above‐mentioned negative changes is  a decrease in the average daily temperature with altitude above sea level  and, as a result, a delay in the accumulation of the sum of effective  temperatures necessary for the passage of certain stages of individual  development and the life cycle as a whole.